2021
DOI: 10.36685/phi.v7i1.388
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Coliform bacteria content in ‘Thai Tea' drinks and its correlation with hygiene factors in Yogyakarta, Indonesia

Abstract: Background: Various water-borne diseases have been seen in developed and developing countries, like  Coliform bacteria in food and drink due to their poor making.Objective: This study aims to estimate the hygiene factors and examine the content of Coliform bacteria and in Thai Tea drinks in Yogyakarta Municipality.Methods: A cross-sectional method was used in all Thai Tea product sellers in Yogyakarta Municipality from September to November 2020. A total of 30 sellers were included, and 30 different types of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…contamination in street foods and drinks in Yogyakarta and elsewhere in Indonesia has not yet been reported. The results of coliform identification on 30 Thai Tea traders and 30 types of Thai Tea drinks with different brands in Yogyakarta showed that the contamination rate exceeded the MPN/100 ml standard (Suryani et al 2021). This study aims to identify the biochemical and molecular isolates of K. pneumoniae isolated from street foods and drinks in Yogyakarta, Indonesia using 16S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%
“…contamination in street foods and drinks in Yogyakarta and elsewhere in Indonesia has not yet been reported. The results of coliform identification on 30 Thai Tea traders and 30 types of Thai Tea drinks with different brands in Yogyakarta showed that the contamination rate exceeded the MPN/100 ml standard (Suryani et al 2021). This study aims to identify the biochemical and molecular isolates of K. pneumoniae isolated from street foods and drinks in Yogyakarta, Indonesia using 16S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%